Store turnover as a predictor of food and beverage provider turnover and associated dietary intake estimates in very remote Indigenous communities - Thomas Wycherley; Megan Ferguson; Kerin O'Dea; Emma McMahon; Selma Liberato; Julie Brimblecombe (Australian and New Zealand Journal of Public Health, 2016)
Abstract Objective: Determine how very‐remote Indigenous community (RIC) food and beverage (F&B) turnover quantities and associated dietary intake estimates derived from only stores, compare with values derived from all community F&B providers. Methods: F&B turnover quantity and associated dietary intake estimates (energy, micro/macronutrients and major contributing food types) were derived from 12‐months transaction data of all F&B providers in three RICs (NT, Australia). F&B turnover quantities and dietary intake estimates from only stores (plus only the primary store in multiple‐store communities) were expressed as a proportion of complete F&B provider turnover values. Food types and macronutrient distribution (%E) estimates were quantitatively compared. Results: Combined stores F&B turnover accounted for the majority of F&B quantity (98.1%) and absolute dietary intake estimates (energy [97.8%], macronutrients [≥96.7%] and micronutrients [≥83.8%]). Macronutrient distribution estimates from combined stores and only the primary store closely aligned complete provider estimates (≤0.9% absolute). Food types were similar using combined stores, primary store or complete provider turnover. Conclusions and implications: Evaluating combined stores F&B turnover represents an efficient method to estimate total F&B turnover quantity and associated dietary intake in RICs. In multiple‐store communities, evaluating only primary store F&B turnover provides an efficient estimate of macronutrient distribution and major food types.